Analisa Penggunaan Sistem Rekrutmen Sumber Daya Manusia Terhadap Kinerja Karyawan Pada PT Maju Pamor Mas JakartaBarat - Arnita Widiandini; Yeni Septiani (Journal of Research and Publication Innovation, 2024)
This research is entitled "Analysis of the Use of the Human Resources Recruitment System on Employee Performance at PT Maju Pamor Mas" and aims to determine the effect of the recruitment system on employee performance in the company. Using quantitative methods and in-depth interviews. The research results show that an effective and efficient recruitment system has a positive impact on employee performance, increasing motivation and productivity. Factors such as job satisfaction, work environment, and employee development programs also play a role in improving performance. This research implies that companies need to continue to improve their recruitment systems and pay attention to other factors that influence employee performance to achieve optimal performance and compete in the market.